ANALISA VARIASI KUAT ARUS ELEKTRODA E6013 TERHADAP SAMBUNGAN LAS PADA PELAT BAJA UNTUK TABUNG GAS 3 KG - Rosidi Rosidi; Budi Yuwono; Darius Yuhas (Politeknik Negeri Jakarta, 2019)
The quality of the welding results is influenced by the qualified welder, the appropriate type of connection, the type of welding, and the electrode. Standard electrode AWS E 6013 with trademark Nikko Steel Welding Elektodes, NK 68 with φ 2.6 mm. The type of camp used is SNI standard 1452-2007 for 3 kg LPG tube. Specimens were subjected to tensile testing, impact toughness, hardness testing, curvature testing, microstructure with current variations of 50 A and 70 A of both types of electrodes used. Welding by SMAW method with circular welding at 3 kg of gas tube blank from JIS G 3116 SG 295 materials. From the test result will be known maximum tensile strength, impact toughness, hardness, curve strength, macro and microstructure. And by comparing the samples of SNI, non SNI and samples from both types of Nikko Steel and NK 68 electrodes, there are differences in mechanical and microstructure characteristics that will significantly affect the toughness of the welding results.